The Effect of Type of Fiber in Density and Splitting Tensile Strength of SIFCON (Journal of Engineering, 2023)
SIFCON is characterized as a construction material of high ductility and very high strength. It is suitable for concrete structures used for special applications. However, the density of SIFCON is much higher than that of Fiber Reinforced Concrete (FRC) due to the need for a large amount of high-density steel fibers. This work examines the split tensile behavior of modified weight slurry infiltrated fiber concrete utilizing a mixture of two types of fibers, steel fiber, and polyolefin fiber. For the investigation, 30 cylinders and 15 cubes were poured. The used volume fraction (V.F) is (6 %) and the use of five series once as each type separately and once a hybrid in proportions of 2/3 polyolefin with 1/3 steel fiber and vice versa. The splitting tensile strength and the unit weight of SIFCON resulting from tests were studied. The results indicate that SIFCON produced from a mixture of 1/3 hook-end steel fibers with 2/3 polyolefin fibers achieved good results in reducing density while maintaining a high split tensile strength. It significantly decreased density by 140 kg per cubic meter and improved splitting tensile strength by 494%.